2015
DOI: 10.1016/j.jnucmat.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution of uranium dioxide following compression creep tests: An EBSD and image analysis study

Abstract: International audienceSintered UO2 pellets with relatively large grains (similar to 25 pm) are tested at 1500 degrees C under a compressive stress of 50 MPa, at different deformation levels up to 12%. Electron Back Scattered Diffraction (EBSD) is used to follow the evolution, with deformation, of grains (size, shape, orientation) and sub-grains. Image analyses of SEM images are performed to characterize emergence of a population of micron size voids. For the considered microstructure and test conditions, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…2b). Damages in the form of inter-granular cavities, have been observed in certain previous studies performed on UO 2 pellets with grain sizes varying from 9 to 36 mm [8,12]. In this study, such damages were only observed at the highest strain rate and level (sample D9), in the central part of the pellet, as illustrated in Fig.…”
Section: Characterization Methodssupporting
confidence: 73%
See 2 more Smart Citations
“…2b). Damages in the form of inter-granular cavities, have been observed in certain previous studies performed on UO 2 pellets with grain sizes varying from 9 to 36 mm [8,12]. In this study, such damages were only observed at the highest strain rate and level (sample D9), in the central part of the pellet, as illustrated in Fig.…”
Section: Characterization Methodssupporting
confidence: 73%
“…Fig. 2b), whereas numerous ones were observed by other authors in pellets deformed under conditions similar to those used in the present work [8,12]. This difference could be related in part to the size of our pellets.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Densities were measured by an immersion method. Grain sizes were measured by EBSD on surfaces of about 0.5 mm 2 , considering a 5 critical disorientation angle for grain boundaries detection [14].…”
Section: Methodsmentioning
confidence: 99%
“…These pellets were submitted to compression creep tests at relatively high stress levels at 1500 C, performed up to mean deformations of the order of 8%. Their microstructures were characterized before and after mechanical test, mainly by scanning electron microscopy (SEM), coupled with image analysis, and electron backscattered diffraction (EBSD), on the basis of a methodology that has been previously implemented on other UO 2 samples [14]. The potential of this approach to determine quantified microstructural characteristics, before and especially after creep tests, is more particularly evaluated.…”
Section: Introductionmentioning
confidence: 99%